Challenges in Harmonising and Implementing the Environmental Crime Directive - Ieva Marija Ragaišytė (Teisė, 2021)
The article analyses the harmonisation framework under TFEU of the Directive 2008/99/EC and the possible difficulties in implementing the document in national legislation. An inadequately chosen legitimate purpose and the lack of the prioritisation of environmental crime in the Member States result in harmonisation and implementation problems related to issues of the definitions of the offences, their differentiation and compliance with fundamental principles of the law.